2005
DOI: 10.1016/j.bbadis.2004.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Elevated formation of pyridinoline cross-links by profibrotic cytokines is associated with enhanced lysyl hydroxylase 2b levels

Abstract: The hallmark of fibrosis is the excessive accumulation of collagen. The deposited collagen contains increased pyridinoline cross-link levels due to an overhydroxylation of lysine residues within the collagen telopeptides. Lysyl hydroxylase 2b (LH2b) is the only lysyl hydroxylase consistently up-regulated in several forms of fibrosis, suggesting that an enhanced LH2b level is responsible for the overhydroxylation of collagen telopeptides. The present paper reports the effect of profibrotic cytokines on the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
73
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 52 publications
1
73
1
Order By: Relevance
“…53 Altered TGF-b storage on fibrilllin-2 containing microfibrils might be responsible for such changes as it was shown that TGF-b influences the cross-linking pathway. 54 In summary, our data show that the enhanced expression of fibrillin-2 is a general feature of activated fibroblasts found either in vivo in wound healing and sclerotic tissues or in cell culture after induction with serum, TGF-b or IL-4. The elevated expression of fibrillin-2 in wound healing and sclerotic tissue is another example for the 'embryonic reprogramming' of fibroblasts in these conditions.…”
Section: Discussionmentioning
confidence: 90%
“…53 Altered TGF-b storage on fibrilllin-2 containing microfibrils might be responsible for such changes as it was shown that TGF-b influences the cross-linking pathway. 54 In summary, our data show that the enhanced expression of fibrillin-2 is a general feature of activated fibroblasts found either in vivo in wound healing and sclerotic tissues or in cell culture after induction with serum, TGF-b or IL-4. The elevated expression of fibrillin-2 in wound healing and sclerotic tissue is another example for the 'embryonic reprogramming' of fibroblasts in these conditions.…”
Section: Discussionmentioning
confidence: 90%
“…PLOD2 is considered a fibrotic marker since its expression and the resulting pyridinoline cross-links are increased in various scarred tissues and in vitro in fibroblast by profibrotic cytokines such as TGF␤1 (4,5,38,43,44). In addition, PLOD2 expression is enhanced in various types of cancers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The results clearly indicate that the transcriptional effects of both inhibitors were TGF␤1 pathway NOVEMBER 20, 2015 • VOLUME 290 • NUMBER 47 related, since no significant effects were observed on the basal PLOD2 expression in unstimulated fibroblasts. The other PLOD family members, PLOD1 and PLOD3, are not responsive to TGF␤1 stimulation (38). To prove that their transcriptional activation is independent on SP1 and SMAD3, we analyzed mRNA expression of PLOD1 and PLOD3 after treatment with SIS3 and Mithramycin A.…”
Section: Tgf␤1-induced Plod2 Expression Depends On Alk5 Andmentioning
confidence: 99%
“…LH2b converts the lysine in the telopeptides into hydroxylysine, thereby inducing the hydroxyallysine route. This route lead to an elevation in pyridinoline crosslinks that results in greater resistance of collagen to enzymatic degradation (14,34,37). Interestingly, both LH2b and pyridinolines are elevated in various fibrotic tissues and organs (34,38).…”
Section: Discussionmentioning
confidence: 99%